Effect of Magnesium Variation on Microstructure and Mechanical Properties of Aluminum Recycled Alloys - Muliastri, Destri; Ruardhian, Mahir; Azmy, Ilham (Mechanical Engineering Department - Semarang State Polytechnic, 2025)
The use of recycled aluminum (scrap) as a lightweight material in the automotive industry continues to grow, especially through the addition of magnesium elements to improve mechanical properties. This study analyzes the effect of adding magnesium of 5 Wt% and 10 Wt% on the mechanical properties and microstructure of aluminum scrap melting results using the sand casting method at a temperature of 707°C. The test results show that the addition of magnesium increases the hardness from 39.4 HV to 94.6 HV, and the tensile strength from 49.5 MPa to 181.5 MPa. Microstructural analysis shows the formation of more Mg phases in the aluminum matrix, resulting in a stronger and more homogeneous structure. The addition of 10 Wt% magnesium gives the most optimal results, proving that recycled aluminum has great potential to be used as a high-value engineering material through an alloying process.